Sekonder anetoderma ile seyreden multipl pilomatriksomalı bir olgu - (:unkn) unknown (My University, 2009)
Pilomatriksoma, kıl follikülü matriks hücrelerinden köken alan selim bir deri tümörüdür. Genellikle soliter bir nodül veya kist şeklinde görülür. Multipl lezyonlar nadirdir ve olguların çoğunda ailede de pilomatriksoma öyküsü bulunur. Pilomatriksoma ile ilişkili anetodermik değişiklikler nadiren tanımlanmıştır. Burada, altı adet pilomatriksoması olan ve ailesinde benzer lezyon bulunmayan onsekiz yaşında bir kız sunulmaktadır. Sırt ve kolda lokalize olan toplam üç tümör üzerinde sekonder anetoderma özellikleri gözlenmiştir.

Pilomatrixoma is a benign skin tumour originating from hair matrix cells. It usually presents as a solitary nodule or cyst. Multiple lesions are rare and are familial in majority of cases. Anetodermic changes overlying pilomatrixomas have rarely been described. We report here an 18-year old girl with six pilomatrixomas. None of her family members had similar lesions. Three of the lesions which were located on the back and arm showed features of secondary anetoderma.
Secondary anetoderma overlying multiple pilomatrixomas: A case report
Keywords: Dermatoloji